Greenwashing and its Consequences in Brand Equity: A Systematic Bibliometric Review - Adhikari, Ujjwal (Journal of Business and Management, 2024)
Background: Greenwashing has been increasingly popular in recent decades. Companies have used eco-friendly marketing approaches to convey their environmental initiatives, aiming to enrich their competitive advantage and attract consumers with ecological awareness. However, there is still a need for extensive and rigorous study, particularly on the emergence of this phenomena and its consequences on brand equity.Objectives: To identify the existing studies on greenwashing, noting gaps and recommending future study opportunities.Methods: The bibliometric study includes 576 items from the “Web of Science” database and “VOSviewer” software was used for analysis. Literature review is based on 12 papers that are highly significant to the study.Results: Analyzing the latest research, this study identifies gaps that can guide future investigations. Potential avenues for further exploration include the influence of greenwashing on consumer buying intentions, attitudes, online business, stakeholders, and cross-cultural aspects.Conclusion: In summary, this study highlights the damaging effects of greenwashing practices on organizations’ brands and images. By analyzing past, present, and future research areas, it underscores the importance of raising awareness to reduce greenwashing acts. Overall, this study helps to better understand the implications of deceptive environmental practices and advocates for greater accountability in promoting environmental responsibility.